What is The Teacher's View of The Development of Digital Teaching Materials in Indonesian Language Learning in Middle Schools? - Vivi Indriyani; Eni Kurniawati; Ary Ramadhan (Jayapangus Press, 2023)
One of the digital technologies that is developing in the world of education is digital teaching materials to support learning. These teaching materials are useful for assisting the learning process and facilitating students with different learning styles. However, current teaching materials are still dominated by printed teaching materials, so innovation in learning is necessary. Based on this, the aim of this research is to determine teachers' responses and views regarding the development of digital teaching materials in Indonesian language learning in secondary schools. This research is descriptive research using survey methods. The population of this study consisted of Indonesian language teachers in West Sumatra who taught at the secondary school level. The sample for this research was 118 teachers. In this research, samples were taken from the population using purposive sampling. The instrument used was a questionnaire. The instrument was developed via the Google Form application and distributed using the WhatsApp application media. The results of the research show that the teaching materials currently used by teachers are in accordance with student characteristics, are contextual and support language skills learning and are project-based. However, these teaching materials still need to be developed and simplified because students still have difficulty understanding the available material. Apart from that, the teaching materials are also not yet interactive and contain learning videos that can facilitate students' different learning styles. Furthermore, the P5 project in Indonesian textbooks is still limited and needs further development.